Investigation of kink induced defect in aluminium sheets for Glare manufacturing. (October 2019) - Nardi, D.; Abouhamzeh, M.; Leonard, R.; Sinke, J.
Abstract: The quality control of Glare panels manufacturing is an important and complex process including the evaluation of the quality of the basic constituents, namely the aluminium sheets, and the glass fibre reinforced pre-preg. In particular, the handling of aluminium sheets is one of the most critical steps for the manufacturing of Glare laminates. The unintentionally induced deformations, referred to as kinks, can significantly affect the geometry and the mechanical properties of the final laminate. This paper considers the effects of kinks in Glare laminates by developing a comprehensive investigation based on controlled kink manufacturing in aluminium sheets, non-destructive and destructive evaluation of laminates with kinks, and the impact on the compressive ultimate strength. The results contribute to the understanding of the kink induced defects and to define thresholds for improving future automated laminate manufacturing.